COVID-19: THE ‘NEW NORMAL’ IN HIGHER EDUCATION - Nurninashahawana Hj Osmara (UIN ANTASARI BANJARMASIN, 2021)
Since the early 2020, the pandemic Covid-19 has devastated effects towards the society, ecosystem and the world itself. This leads to the major interruption of education system where the academic world is forced into a virtual learning experience. Consequently, the digital way of teaching and learning has become mandatory for each level of education especially the higher education institutions in order to prevent community transmission among themselves and to protect their health and safety.Thus, it is very significant for both academicians and students to adapt to virtual teaching and learning in order to perform well and sustain in the education system. In light of this paper, the impact of the pandemic towards the education system which leads to the issue of ‘new normal’ will be analyses in conjunction with the rapidly changing education environment through the usage of technology. Moreover, it is discovered that the higher education institutions are require to obtain knowledge through virtual learning. In order to produce reliable information for this study, the analysis of quantitative and secondary data from reliable sources regarding the following issue has been conducted. The study conducted an online questionnaire to 150 samples of local higher institution students to observe the challenges occur during virtual learning. Hence, this consider as the responsibility of the relevant authorities to address this issue. Nevertheless, this pandemic has its own wisdom in which a plethora of new things has been discovered along with the new prospects of life. Ultimately, this can be confrontedwith the adaptation of the ‘new normal’ gradually. Hence, it is important for the society to be familiarized with the new environment alongside the expeditiously-paced technology. Therefore, it is crucial for the authorities and higher education institutions to strategize accordingly in order to sustain the quality of the education.